2007
DOI: 10.1021/cm071330m
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Spillover on CeO2/Pt: Enhanced Storage of Active Hydrogen

Abstract: We have investigated the concept of hydrogen spillover by a density functional theory (DFT) approach in combination with experimental observations. A H/Pt molar ratio of 5 to 9 is observed over Ce 1-x Pt x O 2-δ catalyst, where Pt is present in the +2 ionic state. The total hydrogen adsorbed over the catalyst is ∼30 times higher than that over nano-Pt metal particles. NMR study show protonic hydrogen over the catalyst. DFT calculations indeed support the enhanced adsorption of hydrogen on the Pt-ion-doped ceri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
75
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 17 publications
9
75
0
Order By: Relevance
“…It was reported that surface cationic Pt species promote dissociation of H 2 and facilitate hydrogen spillover on Pt-doped CeO 2 powders prepared by the solution combustion method. 114 The origins of this reactivity, however, remained obscure.…”
Section: Supported Single Metal Atoms In the Absence Of Metal Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that surface cationic Pt species promote dissociation of H 2 and facilitate hydrogen spillover on Pt-doped CeO 2 powders prepared by the solution combustion method. 114 The origins of this reactivity, however, remained obscure.…”
Section: Supported Single Metal Atoms In the Absence Of Metal Particlesmentioning
confidence: 99%
“…in the absence of other active species such as Pt 4+ , Pt 0 , and oxygen vacancies. [114][115][116] Using well-defined model catalysts, atomically dispersed Pt 2+ species can be prepared and studied individually. 21,99 The corresponding approach involves the preparation of Pt-CeO 2 films with low Pt loading at low temperature followed by brief annealing to 700 K. 21 The same procedure allows the preparation of atomically dispersed Pd 2+ and Ni 2+ species on nanostructured ceria.…”
Section: Supported Single Metal Atoms In the Absence Of Metal Particlesmentioning
confidence: 99%
“…However, it has been shown, for ionic Pt in CeO 2, that more than one H atom can be stabilized over a single Pt ion. 32 Therefore, step (1h) in the above equation takes place over a single site and, hence, the above set of equations can be lumped into a single equation (Eq. 1f) without affecting the kinetics of the reaction.…”
Section: Structural Studiesmentioning
confidence: 99%
“…The low-temperature desorption peaks (centred at 60 8C) are ascribed to the hydrogen adsorbed on the surface of Pt, and the high temperature desorption peaks nearly 400 8C are assigned to spillover hydrogen. [14] The intensity of the lowtemperature peak of 2Al-Pt-in-ANTsi sl ess than that of Pt-inANTs. The H 2 uptake ( Table 2) relatedt ot he low temperature of 2Al-Pt-in-ANTs (1.81 mmol g À1 -Pt) is approximately 47 % smaller than that of Pt-in-ANTs( 3.44 mmol g À1 -Pt), indicating that 2Al-Pt-in-ANTs has al ower exposed fractiono fP ta tom than that of Pt-in-ANTs.…”
mentioning
confidence: 96%